Glide symmetry breaking and Ising criticality in the quasi-1D magnet CoNb2O6 - Fava, M; Coldea, R; Ashok Parameswaran, S (National Academy of Sciences, 2020)
We construct a microscopic spin-exchange Hamiltonian for the quasi–one-dimensional (1D) Ising magnet CoNb2O6 that captures detailed and hitherto-unexplained aspects of its dynamic spin structure factor. We perform a symmetry analysis that recalls that an individual Ising chain in this material is buckled, with two sites in each unit cell related by a glide symmetry. Combining this with numerical simulations benchmarked against neutron scattering experiments, we argue that the single-chain Hamiltonian contains a staggered spin-exchange term. We further argue that the transverse-field–tuned quantum critical point in CoNb2O6 corresponds to breaking this glide symmetry, rather than an on-site Ising symmetry as previously believed. This gives a unified microscopic explanation of the dispersion of confined states in the ordered phase and quasiparticle breakdown in the polarized phase at high transverse field.